Evaluation of OUM's Web-Based HTML Modules from the Theoretical and Practical Perspective towards proposing an Improved Model - Lim, Tick-Meng; Widad Othman; Woo, Tai-Kwan; Safiah Md Yusof; Halimatolhanin Mohd Khalid (-, 2011)
Open University Malaysia (OUM) is an open and distance learning (ODL) institution in Malaysia. It adopts a blended learning mode of instructional delivery which comprises three components: self managed learning using the print modules, online learning and face-to-face instruction. The self-managed learning component constitutes about 80% of the estimated learning time and the print module is the main resource used by learners to guide their learning. In the past two years, the University has been embarking on a major project of converting all its print modules to the web-based HTML modules. This research study was carried out to determine the efficacy of the web-based HTML modules as a self-managed learning tool. This research study research adopted a twophase approach. In the first phase, the modules were thoroughly examined by the researchers to determine the extent to which the web-based HTML modules comply with criteria of an effective learning tool from the theoretical perspective. The examination revealed a number of missing elements which are essential for effective online selfmanaged learning. Subsequently, a survey was conducted in the second phase to depict users' ratings (OUM learners) on the adequacy of the modules from the technical, interface-design, learner-support and instructional perspective. Design of Items for evaluating the adequacies were closely guided by the seven principles of good practice in undergraduate education (Chickering and Gamson ,1987). Research results reveal that that the web-based HTML modules are generally perceived by learners to be a useful self-managed learning tool. Pearson Product correlation calculated shows that the learners' perceptions on the adequacies of the modules have weak correlations with their competencies in ICT despite the fact that using web-based modules may require some knowledge or skills in ICT. T-test conducted also reveals that there is only slight difference between male learners and female learners towards the perceived quality of the modules. Examination form the theoretical perspective together with feedbacks from the users however help to identify some missing but necessary elements for effective learning. Based on the analyses, a revised conceptual framework for the design and development of the revised web-based interactive modules (WebIM) was proposed. (Executive summary)